CREATIVE AND INNOVATIVE LANGUAGE TEACHING - Uktamova Nilufar Nozimjon kizi; Berdikulova Munira Azizovna (PEDAGOGS, 2024)
Abstract: The accomplishment of language learning objectives is mutually supported by the importance of both creativity and innovation in language instruction. Both the content offered and how teachers convey it to their students determine how successful language instruction is. In this instance, the content is prepared in compliance with the curriculum's guidelines, taking into consideration the content that is relevant to the situation to meet the learning objective. From here, lesson plans that spark students' interest, inventiveness, and inventions develop into vital diagrams that educators must create before beginning lessons in the classroom. As a result, this article offers some ideas for developing original and creative language instruction.1